Motivasi Petani dalam Mengikuti Program Penanaman Refugia di Kecamatan Mojolaban, Kabupaten Sukoharjo - Umi Salamah; Sapja Anantanyu; Arip Wijianto (Universitas Sebelas Maret, 2021)
The motivation of farmer is a farmers is a farmer’s encouragement to achieve the desired goals. This study aims to analyze : (1) the motivation of farmers in participating in the refugia planting program in Mojolaban District, Sukoharjo regency (2) factors that influence the motivation of farmers in participating in the refugia planting program Mojolaban Sukoharjo regency (3) the relationship between the factors that influence the motivation of farmers with the motivation of farmers in participating in the refugia planting program in Mojolaban District, Sukoharjo Regency. The basic method of research is quantitative with survey techniques. Determination of the location is deliberately determined, namely the region that runs a refugia planting program in eight villages including Sapen villagr, Joho village dan Palur village. Data analysis using Spearman Rank Correlation Test with the IBM SPSS 23 Program. The result showed that : (1) farmers had high motivation in participating in the refugia planting program (2) the majority of farmers are lowly educated and have a low amount of dependence, the old work of farmers including high, farmers have a social environment and a high economic environment (3) There is a very significant relationship between education, income, and dependents with the motivation of farmers, but there is no significant relationship between work, social environtmen with the motivation of farmers in participating in the refugia planting program in Mojolaban District, Sukoharjo Regency.